Quality Analysis and Improvement of Nut Dragging Defects in FR S/C Side RH Bracket Products within Indonesia's Automotive SMEs - Sumasto, Fredy; Saputra, Yogi Pangestu; Imansuri, Febriza; Marizka, Dewi Auditiya; Ismono, Ahlan; Rozi, Muhamad Fahrul (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2024)
This study analyses the quality of FR S/C Side RH Bracket products at PT BMI, especially concerning the nut dragging problem, which is often the main defect. This study aims to analyze and improve the nut dragging defect problem in FR S/C Side RH Bracket products, as well as provide an understanding of the effectiveness of the improvement in reducing the number of defective products. The analysis shows that FR S/C Side RH Bracket products with nut dragging problems are the most frequent defects, reaching 632 defective units or about 60% of the total defective products before improvement. The Failure Tree Analysis (FTA) method was used to identify the root cause of the nut dragging problem, which revealed that machine factors were generally the main cause, especially setting the spot welding machine parameters too high. In response, improvements were made by changing the parameters on the SW.03 spot welding machine and adding a cooling water line. The results showed a significant decrease in defective products, totaling 1320 units. After the improvement, only 141 units were defective. This research provides an in-depth understanding of product quality issues at PT BMI. It offers solutions to improve product quality and meet customer expectations in the highly competitive automotive industry.